Dentinogenesis imperfecta type II: approach for dental treatment - Raquel Mantuaneli Scarel-Caminaga; Lícia Bezerra Cavalcante; Livia Sertori Finoti; Maria Cristina Leme Godoy dos Santos; Maria Flávia Konishi; Lourdes Aparecida Martins dos Santos-Pinto
INTRODUCTION: Dentinogenesis imperfecta (DI) is a hereditary dentin development disorder that affects both primary and permanent dentitions. The DI characteristics are discolored and translucent teeth ranging from gray to brownish-blue or amber. The enamel may split readily from the dentin when subjected to occlusal stress. Radiographically there are evident of cervical constrictions, short root and pulp chambers, and the root canals are smaller than normal or completely obliterated. The dental treatment choice can be decided on a case-by case‑basis, considering the degree of dental tissue loss, and child age and cooperation. OBJECTIVE: The aim of this case report was to describe the early dental treatment performed in a child affected by DI type II. CASE REPORT: The treatment involved basic preventive procedures. Primary molars were worn to such an extent that the remained tooth structure was covered with composite resin to protect the exposed dentin. Resin-based sealant was applied in all first permanent molars. Posterior cross bite was treated with the expansion of the upper arch. CONCLUSION: The early treatment restored the patient´s vertical dimension resulting in acceptable esthetics and function for the permanent teeth to complete their eruption.